A novel W/O/W double emulsion co-delivering brassinolide and cinnamon essential oil delayed the senescence of broccoli via regulating chlorophyll degradation and energy metabolism. (15th September 2021) - Huang, Hao; Wang, Di; Belwal, Tarun; Dong, Li; Lu, Ling; Zou, Ying; Li, Li; Xu, Yanqun; Luo, Zisheng
Highlights: W/O/W double emulsion is formed by whey protein concentrate-high methoxyl pectin. The double emulsion co-encapsulates brassinolide and cinnamon essential oil. The double emulsion keeps chlorophyll of broccoli by inhibiting degrading enzymes. High energy supply is also maintained by activating SDH, CCO, and ATPases. Abstract: The postharvest senescence accompanied by yellowing limited the shelf-life of broccoli. In this study, we developed a novel W/O/W double emulsion co-delivering brassinolide and cinnamon essential oil and applied it to broccoli for preservation. Results showed that double emulsion prepared by whey protein concentrate-high methoxyl pectin (1:3) exhibited best storage stability with largest particle size (581.30 nm), lowest PDI (0.23) and zeta potential (−40.31 mV). This double emulsion also exhibited highest encapsulation efficiency of brassinolide (92%) and cinnamon essential oil (88%). The broccoli coated with double emulsion maintained higher chlorophyll contents and activities of chlorophyllase and magnesium-dechelatase were reduced by 9% and 24%, respectively. The energy metabolic enzymes (SDH, CCO, H + -ATPase, Ca 2+ -ATPase) were also activated, inducing higher level of ATP and energy charge. These results demonstrated W/O/W double emulsion co-delivering brassinolide and cinnamon essential delayed the senescence of broccoli via regulating chlorophyll degradation and energy metabolism.